Women in leadership: a systematic literature review of Middle Eastern women managers' careers from NHRD and institutional theory perspectives. Issue 1 (1st January 2022) - Abadi, Mehrangiz; Dirani, Khalil M.; Rezaei, Fatemeh Dena
ABSTRACT: Middle Eastern (ME) societies have witnessed a growing demand for career growth and leadership roles by women. The current article is a systematic literature review on the challneges of ME women managers and leaders' career growth. This article is guided by three objectives: a) to identify scholarly articles published on ME women leadership careers after the expansion of women's associations in the 1980s, b) to identify and synthesize major challenges faced by the Middle Eastern women managers and leaders through a thematic analysis of literature informed by Institutional Theory (INT), and c) to identify gaps and propose guidelines for HRD at organizational and national levels with respect to practice and research. Institutional theory undergirds the present review paper and accounts for the complexity of a diverse set of socio-cultural values and norms, as well as organizational policies that shape the overall experience of the Middle Eastern women managers and leaders. Findings provide HRD researchers with a deeper understanding of National HRD (NHRD) systems, policies, and practices in the Middle Eastern context. In addition, it provides national policymakers, educators, human resource professionals, and academic researchers with a deeper understanding of how HRD is conceptualized in developing societies within the Middle East.